Clinical Outcomes of Stereotactic Radiosurgery for Cerebral Arteriovenous Malformations in Pediatric Patients: Systematic Review and Meta-Analysis. Issue 4 (27th May 2019) - Börcek, Alp Özgün; Çeltikçi, Emrah; Aksoğan, Yiğit; Rousseau, Matthew John
Abstract: BACKGROUND: Arteriovenous malformations (AVMs) in pediatric patients exhibit remarkable differences in terms of management and outcomes. Owing to a paucity of relevant data pertaining to AVMs in pediatric patients, special interest and investigation are required for an improved understanding of the available evidence by clinicians. OBJECTIVE: To determine the clinical outcomes of single-session stereotactic radiosurgery (SRS) for AVMs in pediatric patients. METHODS: A systematic literature review was performed to identify studies that reported the outcomes of SRS for AVMs in pediatric patients. Data pertaining to variables such as obliteration rate, post-SRS new hemorrhage rate, post-SRS new neurological deficit rate, and mortality rate were extracted and analyzed using meta-analysis techniques. RESULTS: Based on pooled data from 20 studies with 1212 patients, single-session SRS resulted in complete obliteration in 65.9% (95% confidence interval [CI], 60.5%-71.1%; I 2  = 66.5%) patients. Overall complication rate (including new hemorrhage, new neurodeficit, and mortality) was 8.0% (95% CI, 5.1%-11.5%; I 2  = 66.4%). Post-SRS new neurological deficit rate was 3.1% (95% CI, 1.3%-5.4%; I 2  = 59.7%), and post-SRS hemorrhage rate was 4.2% (95% CI, 2.5%-6.3%; I 2  = 42.7%). There was no significant difference between studies disaggregated by treatment method (Gamma Knife [Elekta AB] vs other), treatment year (before year 2000 vs after year 2000), median AVM volume reported (≥3 vs <3 cm 3 ), median dose reported (≥20 vs <20 Gy), or follow-up period (≥36 vs <36 mo). CONCLUSION: Single-SRS is a safe treatment alternative that achieves high obliteration rates and acceptable complication rates for AVMs in pediatric patients.